Regulation of von Willebrand factor-platelet interactions - Lenting, Peter J.; Pegon, Julie N.; Groot, Evelyn; de Groot, Philip G. (Thrombosis and Haemostasis, 2010)
The formation of thrombi is a multistep process involving several components, including von Willebrand factor (VWF). VWF is an adhesive multimeric protein, which acts as a molecular bridge between the subendothelial matrix and the glycoprotein Ib/IX/V receptor complex. Furthermore, VWF promotes the expansion of the platelet plug by cross-linking platelets via binding to integrin αIIbβ3. In terms of thrombus formation, it is essential that VWF-platelet interactions occur timely, that is: it should happen not too early or too late. Given the co-existence of VWF and platelets in the circulation, this implies that there must be regulatory mechanisms that prevent premature formation of VWF-rich platelet aggregates that could occlude the vasculature. Indeed, several mechanisms have been identified at the level of VWF, which are dedicated to the prevention of excessive VWF-platelet interactions following endothelial release of VWF (which may include limited exposure to shear stress, the presence of Mg2+ ions, inhibition of VWF-platelet interactions by endothelial proteins, ADAMTS13-mediated proteolysis) and of circulating VWF-platelet aggregates during normal circulation (shielding of the platelet-binding A1 domain by other regions of the VWF molecule, inhibition of VWF-platelet interactions by β2-glycoprotein I). In the present review an overview of these mechanisms will be discussed.
Keywords: Von Willebrand factor; thrombosis; von Willebrand disease